A digital mental health intervention to reduce depressive symptoms among overseas Filipino workers: protocol for a pilot hybrid type 1 effectiveness-implementation randomized controlled trial - Liem, Andrian (Implement Sci Commun, 2020)
BACKGROUND: The current pilot randomized controlled trial (RCT) protocol will comprehensively describe the implementation of a culturally adapted Filipino version of the World Health Organization Step-by-Step (SbS-F) program, unguided online psychological intervention for people with depression based on behavioral activation, among overseas Filipino workers (OFWs) in Macao (Special Administrative Region). The main objective of this pilot study is to explore the preliminary effectiveness of the SbS-F program to decrease participant-reported depressive symptoms compared to enhanced care as usual (ECAU); and the secondary objectives are to explore the preliminary effectiveness of the SbS-F to decrease participant-reported anxiety symptoms and improve wellbeing, and to evaluate the potential for SbS-F implementation in real-world settings. METHODS: This trial will follow an effectiveness-implementation hybrid type 1 trial design and utilize the Reach, Efficacy/Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework to accelerate the translation of clinical research into more effective implementation strategies and policies. Participants will be randomized 1:1 to control and treatment groups. Control group participants will receive ECAU that consists of brief depression psychoeducation and referral to local community partners. Treatment group participants will receive a 5-session of digital intervention through a mobile phone application. The primary outcome (depression) and psychological secondary outcomes (anxiety symptoms and wellbeing) will be measured using validated instruments. To evaluate study implementation, an embedded mixed-methods design will be used to collect data from various stakeholders. Data then will be analyzed using intention to treat principle and reported following the Consolidated Standards of Reporting Trials (CONSORT) guideline. DISCUSSION: This study will provide important new knowledge about the preliminary effectiveness of SbS-F, a mobile application, as a digital mental health intervention and its scalability. If SbS-F shows positive results among OFWs in Macao, it has strong potential to be used by OFWs in other countries that may also experience depression and difficulty accessing mental health services. TRIAL REGISTRATION: Prospective registration, Chinese Clinical Trial Registry (ChiCTR2000034959) on 26/07/2020.